Currency Convertibility in the Economic Community of West African States - Nsouli, Saleh (Occasional Papers; Occasional Paper ;, 1982)
One of the principal aims of the effort to integrate the economies of the 16 member countries of the Economic Community of West African States (ECOWAS) is to expand intra-Community trade. This objective is to be achieved partly through the elimination of quantitive and other restrictions on trade.